Preparing parent leaders as co/instructors in higher learning for teacher education - Johnson, Mary L. (Parent advocate) (Emerald Publishing Limited : IAP | Information Age Publishing, Inc., 2023)
"This book is a first person narrative from a parent/community advocate. Examining my personal experiences as a parent of color in a Higher Learning Institute, I highlight some of the frustrations experienced by urban working class parents of color as they attempt to engage teachers in their community's schools. I underscore the importance of one community organization in Los Angeles, called Parent U-Turn that works to equip novice teachers for the challenges they will face. Parent-U-Turn offers outreach strategies focused not only on improving "parenting skills" to parents but also on providing teachers with the tools and skills they need to effectively advocate and outreach to urban families and their children. I conclude by presenting seven strategies for novice teachers who want to improve and be successful in urban schools. The majority of these strategies are grounded in my own personal experiences, thus are action research based. In addition to my experiences with my own children, I draw upon my experiences working with Teacher Of America, Ucla Center X Teacher ED Program and parents in LAUSD and Lynwood USD to promote activism by parents so that their voices are heard for the benefit of low-income children. The seven stages of teacher strategies seek to create a new model and perspectives for teacher preparation programs that include All teachers in our ethnically and linguistically diverse schools/communities for the 21st Century"--